Sell in May and Go Away or Just Another January Effect? Studied of Anomaly in Indonesia Stock Exchange - Restu Hayati; Mimelientesa Irman; Lintang Nur Agia (International Journal of Economics Development Research (IJEDR), 2020)
Sell in May and go away is a phenomenon of return anomaly that starts in May and lasts until October. These months are called the worst months of stocks. Conversely, the months of November to April are often referred to as the best months of the stock where a higher rate of return is achieved throughout the year. Although it has not been proven academically, this phenomenon has been mentioned by various media in Indonesia such as Kontan, CNN Indonesia, and Tempo Business which are predicted to correct the JCI throughout 2017. The purpose of this study is to prove the phenomenon of sell in May and go away on the Indonesia Stock Exchange, and find out whether the average best return of the month is affected by the high return in January. The results prove that even though the average returns increase in November-April was due to the high return in January, but there was no sell in May and go away on the Indonesia Stock Exchange. Under these conditions, the direction of the relationship between risk and return is the opposite that directs the Indonesia Stock Exchange to the efficient market hypothesis.